Jesus Fulfils the Law - Anonymous (Salt Lake City, UT : Project Gutenberg, 2011)
"Jesus Fulfils the Law" by Anonymous is a theological treatise written in the late 19th century. The book explores the fulfillment of Old Testament laws and prophecies through the life and ministry of Jesus Christ, emphasizing the transition from the Mosaic law to the new covenant established in the Gospel. It is likely aimed at a Christian audience seeking to understand the scriptural connections between the law, Judaism, and the teachings of Christianity. The text is structured into several chapters that discuss key themes such as the nature of Jesus's fulfillment of the law, the significance of various Hebrew sacrifices, and the prophetic evidence of Jesus as the Messiah. The author argues that Christ$1 (Bs life and sacrifice provide the true complement to the Old Testament sacrificial system, which was ultimately unable to grant eternal reconciliation and atonement. By examining Christ's role as both Apostle and High Priest, the book illustrates how the New Covenant offers a more profound understanding of God's will and mercy, asserting that belief in Jesus is essential for salvation and spiritual enlightenment. (This is an automatically generated summary.)s
How Jesus fulfilled the law -- Provisions for the pardon of sin, and reconciliation under the law -- The Hebrew sacrifices from the Christian point of view. The sacrifice of Christ their true complement -- Testimony of the Old Testament prophecies to Jesus Christ as the Messiah -- The Gospel of Christ.
Release date is 2011-06-14
Transcribed from the 1882 Saml. Harris & Co. edition by David Price
Keywords: Jesus Christ